PEMEROLEHAN KLAUSA RELATIF PADA PEMELAJAR BAHASA INDONESIA BAGI PENUTUR ASING (BIPA): KAJIAN BAHASA-ANTARA - Suharsono, Suharsono (LITERA, 2015)
Abstract This study aims to describe the acquisition of relative clauses by BIPA (Bahasa Indonesia for Foreigners) learners of the intermediate level, in terms of: (a) relative clause forms, (b) the sequence of relative clause acquisition, and (c) effects of language learning strategies on the relative clause acquisition. The data were collected from the use of Indonesian by BIPA learners attending a language program and through a questionnaire. The language data were analyzed by the translational equivalence and distributional methods and the questionnaire data by the calculation of means and percentages presented in tables and graphs. The results of the study showed that the use of the relative pronoun yang was the item with the lowest acquisition level and the relative clause type relativizing the subject was in the highest rank. Meanwhile, the use of language learning strategies had a positive correlation with the relative clause acquisition. The study concludes that: (1) the sequence of the relative clause acquisition reflects both the sequence of mastery and the difficulty level of of each clause type, and (2) the use of language learning strategies enables learners to acquire relative clauses faster.